2020
DOI: 10.35848/1347-4065/ab70a6
|View full text |Cite
|
Sign up to set email alerts
|

85% endurance error reduction and data-retention lifetime enhancement by changing the reset voltage in 40 nm TaO X -based ReRAM

Abstract: This paper proposes a changing reset voltage technique for 40 nm TaOX-based resistive random access memories (ReRAM). In the proposed technique, reset voltage (VRESET) changes at high endurance such as 104 set/reset cycles. The changing reset voltage technique decreases the measured total bit-error rate (BER) of both the low resistance state (LRS) and high resistance state (HRS) by 85%, compared with conventional fixed reset voltage. In addition, the current difference between LRS and HRS at probability = 50% … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 24 publications
(33 reference statements)
0
1
0
Order By: Relevance
“…3,16) In terms of a ReRAM device, on the one hand, a ReRAM device has reliability issues because ReRAM causes bit-error at high Set/Reset cycles. 15,17,18) On the other hand, as for biterror in SA, it has been reported that searching the optimal answer by controlling the device noise properly is more accurate. 13) Therefore, by co-design of a ReRAM device and log-encoding SA, the influence of the asymmetric ReRAM error characteristics and bit precision on SA is analyzed.…”
Section: Introductionmentioning
confidence: 99%
“…3,16) In terms of a ReRAM device, on the one hand, a ReRAM device has reliability issues because ReRAM causes bit-error at high Set/Reset cycles. 15,17,18) On the other hand, as for biterror in SA, it has been reported that searching the optimal answer by controlling the device noise properly is more accurate. 13) Therefore, by co-design of a ReRAM device and log-encoding SA, the influence of the asymmetric ReRAM error characteristics and bit precision on SA is analyzed.…”
Section: Introductionmentioning
confidence: 99%